2022
DOI: 10.3390/ijms23084116
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence Variation in GmBADH2 Enhances Soybean Aroma and Is a Functional Marker for Improving Soybean Flavor

Abstract: The vegetable soybean (Glycine max L. Merr.) plant is commonly consumed in Southeast Asian countries because of its nutritional value and desirable taste. A “pandan-like” aroma is an important value-added quality trait that is rarely found in commercial vegetable soybean varieties. In this study, three novel aromatic soybean cultivars with a fragrant volatile compound were isolated. We confirmed that the aroma of these cultivars is due to the potent volatile compound 2-acetyl-1-pyrroline (2AP) that was previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The authors developed PCR-based SNP markers for utilization in breeding programs. This was recently confirmed by Qian et al [ 113 ] in three novel aromatic vegetable soybean varieties (QX1, ZK1754, and XD). The pandan-like fragrant variety Chiang Mai 84-2 has been developed to replace the variety Kaori for export to Japan [ 43 ].…”
Section: Technological Interventions To Address the Constraintssupporting
confidence: 59%
“…The authors developed PCR-based SNP markers for utilization in breeding programs. This was recently confirmed by Qian et al [ 113 ] in three novel aromatic vegetable soybean varieties (QX1, ZK1754, and XD). The pandan-like fragrant variety Chiang Mai 84-2 has been developed to replace the variety Kaori for export to Japan [ 43 ].…”
Section: Technological Interventions To Address the Constraintssupporting
confidence: 59%
“…As shown in previous studies [ 4 , 15 , 17 , 24 , 38 ], the BADH2 gene can be mutated by the loss of two bases in the 10th exon, three SNPs and the deletion of eight bases in the seventh exon, or a seven-base deletion in the second exon. Our analysis of the BADH2 gene sequence revealed that the similar mutation is present in ZK1754, in which there are two TT deletions in the tenth exon.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, the mutations in OsBADH1 also give rise to aroma in rice [ 14 , 22 ]. Similarly, in aromatic soybeans, a 2-base (TT) deletion in exon ten of GmBADH2 (Glyma05g01770) results in a premature stop codon, leading to non-functional GmBADH2 [ 23 , 24 ]. Suppression of the expression of the GmBADH2 gene by RNAi or CRISPR-Cas9 also confers aroma to non-aromatic soybean [ 4 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, GmBADH2 was functionally characterized using a CRISPR-Cas9 system with improved aroma in Tianlong No. 1 cultivar . Sorghum, the fifth largest cereal crop in the world, also has one copy of the SbBADH2 gene.…”
Section: Progress In Omics Technology-mediated Genome Editing In Plantsmentioning
confidence: 99%